Development and Characterization of Transferosome-Based Topical Formulation Incorporating Centella Asiatica for Enhanced Wound Repair and Skin Regeneration - Pandey, Rajlakshmi; Sharma, Vikas Chandra (Journal of Neonatal Surgery, 2025)
The present study focuses on the formulation and evaluation of a transferosome-based topical delivery system incorporating Centella Asiatica for enhanced wound healing and skin regeneration. Transferosomes, as highly deformable lipid vesicles, improve the penetration of bioactive compounds into deeper layers of the skin, overcoming the limitations of conventional formulations. Centella Asiatica is a renowned medicinal plant with potent wound healing properties attributed to its triterpenoid compounds like asiaticoside and madecassoside, which promote collagen synthesis and fibroblast activity. Transferosomes were prepared using the thin-film hydration method and optimized based on particle size (average: 120 ± 4 nm), zeta potential (-28.5 ± 1.5 mV), and entrapment efficiency (85.7 ± 3.2%). The optimized formulation was incorporated into a hydrophilic ointment base and evaluated for physical properties, spreadability, stability, and in-vitro drug release (76.5% in 24 hours). Wound healing efficacy was tested on Wistar rats using excision wound models, showing a significant increase in wound contraction (89.6% in the treated group compared to 62.8% in the control group by Day 14). Histological analysis demonstrated enhanced re-epithelialization, granulation tissue formation, and collagen deposition in the treated group. The results confirm that the transferosome-based delivery system of Centella Asiatica offers a promising approach to improve topical wound healing therapy through enhanced skin penetration and sustained release